Teaching And Learning Narrative Text Writing Through Story Mapping - Rahmawati, Istiqomah Nur; Latifah, Nur (English Education: Jurnal Tadris Bahasa Inggris, 2019)
This research focused on teaching and learning narrative text writing through story mapping. The objectives of this research were to know and describe the process of teaching and learning narrative writing using story mapping and the teacher and students problems in teaching and learning narrative writing through story mapping. In this research, the writer used descriptive qualitative research method. In collecting the data, the kinds of instruments used by the writers were observation, interview, and questionnaire. In data analysis, the writers used data reduction, data display, and conclusion or verification. The writers found that the teacher’s problems in teaching writing through story mapping were the teacher had difficulties to introduce story mapping, giving instruction to create and complete story mapping, many students in the classroo and less time to teach writing. The problems faced by students in learning writing using story mapping were that the students confused and difficult to develop their ideas because they did not have many vocabularies. Furthermore, the students had problems in capitalization, punctuation, grammatical error, and organization. They also needed too much time to finish their writing